Use of alcohol, tobacco and illicit drugs among ethnic Norwegian and ethnic minority adolescents in Hordaland county, Norway: the youth@hordaland-survey. Issue 1 (2nd January 2018) - Skogen, Jens Christoffer; Bøe, Tormod; Sivertsen, Børge; Hysing, Mari
ABSTRACT: Objective : To describe potential differences in unhealthy behaviours among ethnic Norwegian adolescents and minority adolescents from countries within the European Union, European Economic Area or US (EU/EEA countries) and adolescents from non-EU/EEA countries. Specifically, we aimed to investigate ethnic differences in use of alcohol, tobacco and illicit drugs, and potential confounding due to socio-demographic characteristics. Design : Cross-sectional population-based study of adolescents aged 16–19 ( N  = 10, 122), with self-reported ethnicity as grouping variable, and self-reported use of alcohol, tobacco and illicit drugs as dependent variables. Results : We found that minority adolescents from EU/EEA and non-EU/EEA countries differed from ethnic Norwegian adolescents on important indicators of unhealthy behaviours. Compared to Norwegian adolescents, adolescents from EU/EEA were more likely to report having tried to smoke, to be a daily smoker and to ever having tried an illicit drug (adjusted odds ratio (OR) ranging from 2.01 to 3.74). They were, however, less likely to have tried snus (a form of smokeless tobacco; adjusted OR 0.64; confidence interval (CI) 95% 0.43–0.97) and to report daily snus use (adjusted OR 0.31; CI95% 0.15–0.67). There were no differences in having tried alcohol. Non-EU/EEA adolescents were less likely to have ever tried alcohol (OR 0.24; CI95% 0.18–0.31), snus (OR 0.47; CI95% 0.34–0.65) and to smoke (0.68; CI95% 0.52–0.91), and less likely to report daily snus use (OR 0.36; CI95% 0.21–0.62) compared to Norwegian adolescents. There were no differences with regard to having tried illicit drugs and reporting being a daily smoker. All differences observed were robust to adjustment for age, gender and family socio-economic status. Conclusion : The presents study identified important differences in unhealthy behaviours across different ethnic groups in Norway. The differences in the prevalence of unhealthy behaviours among ethnic minorities are still relevant in a public health perspective, and potential mechanisms should be investigated further.